Bonding performance of a self-adhering flowable composite to substrates used in direct technique - Rubens Nazareno Garcia; Andrey Everton Morelli; Beatriz Steinbach da Silva; Bruna Marina Giongo; Camila Pickering Pollheim; Gabriela Schlemper Largura; Laura Fernanda Mensch; Mariana Franco Costa; Nádia Regina Candiotto; Ana Cristina Rocha Gomes (Revista Sul-Brasileira de Odontologia, 2014)
Simplified restorative materials may be a logical next step for dental manufacturers. Objective: The aim of this study was to evaluate the shear bond strength of a self-adhering flowable composite to four substrates used in direct technique. Material and methods: Eighteen samples (5 mm wide, 15 mm length and 2 mm thick) of bovine teeth – uncut enamel/UE, cut enamel/CE, median dentin/MD (6 samples each) – and blocks (also 6 samples) of the nanocomposite/NC Filtek Z350 XT (3M ESPE) were used, and samples of each substrate were divided into two groups (n = 3). Two flowable composites (Control/FF – Filtek Z350 XT Flow/3M ESPE, and the self-adhering/DF – Dyad Flow/Kerr) were bonded to the four substrates. For all groups and in each sample, four Tygon tubings were positioned over the sample, which were filled in with the composites FF and DF, and visible light-cured for 20 s. The tubings were removed to expose the cylinder-shape specimens (12 per group) and samples were stored in relative humidity at 37±2°C for one week. After this period, each sample was attached to testing machine and the specimens were submitted to the shear bond strength test at speed of 1.0 mm/min, until failure. The results were analyzed by two-way ANOVA and Tukey test (p < 0.05). Results: The means (SD) were (in MPa): UE + FF = 20.8 ± 1.0; UE + DF = 23.9 ± 3.1; CE + FF = 22.7 ± 1.8; CE + DF = 29.6 ± 5.4; MD + FF = 24.8 ± 4.5; MD + DF = 20.8 ± 3.2; NC + FF = 25.9 ± 6.2; NC + DF = 28.4 ± 5.1. Conclusion: The efficacy of flowable composites is material-dependent. The self-adhering composite provided higher bond strength on both cut enamel and nanocomposite. Comparing to the control group, Dyad Flow showed lower bond strength to median dentin, however higher bond strength to cut enamel.